Artificial intelligence, academic ethics, and global citizenship - Cathrin, Shely; Rukiyati, Rukiyati; Maryani, Maryani (Universitas Negeri Yogyakarta, 2024)
This research aims to identify ethical-philosophical issues arising from AI technology's presence in the academic world and identify the impact of AI's presence in the academic world on humanity's future as global citizens. This research is important to carry out because of the widespread use of artificial intelligence technology in education, which indirectly exacerbates the problems faced by humans as global citizens. This research serves as a model for investigating philosophical issues within the field. This type of research is often referred to as library research. The research process consists of three stages: data collection, data classification, and data analysis. The methodical elements used are description, language analysis, analytics, synthetics, and interpretation. The research results show: 1) The main ethical and philosophical problems that arise from AI's presence in the academic world are the crisis of human autonomy, the crisis of academic honesty, and the crisis of responsibility. 2) The presence of AI in the academic world impacts the future of humans as global citizens by causing a crisis of academic honesty. This crisis has the potential to escalate into a more serious issue, specifically an academic identity crisis, as the use of artificial intelligence becomes more commonplace in almost all aspects of human life. The presence of AI in the academic realm, particularly in relation to humanity's future as global citizens, intensifies the issue of identity crises.